HIV Drug Resistance-Associated Mutations in Antiretroviral Naïve HIV-1-Infected Latin American Children - Luis E. Soto-Ramirez; Roberto Rodriguez-Diaz; D. Robert Harris; Rohan Hazra (Advances in Virology)
Our goal was to describe the presence of HIV drug resistance among HIV-1-infected, antiretroviral (ARV) naïve children and adolescents in Latin America and to examine resistance in these children in relation to drug exposure in the mother. Genotyping was performed on plasma samples obtained at baseline from HIV-1-infected participants in a prospective cohort study in Brazil, Argentina, and Mexico (NISDI Pediatric Study). Of 713 HIV-infected children enrolled, 69 were ARV naïve and eligible for the analysis. At enrollment, mean age was 7.3 years; 81.2% were infected with HIV perinatally. Drug resistance mutations (DRMs) were detected in 6 (8.7%; 95% confidence interval 3.1–18.2%) ARV-naïve subjects; none of the mothers of these 6 received ARVs during their pregnancies and none of the children received ARV prophylaxis. Reverse transcriptase mutations K70R and K70E were detected in 3 and 2 subjects, respectively; protease mutation I50 V was detected in 1 subject. Three of the 6 children with DRMs initiated ARV therapy during followup, with a good response in 2. The overall rate of primary drug resistance in this pediatric HIV-infected population was low, and no subjects had more than 1 DRM. Mutations associated with resistance to nucleoside reverse transcriptase inhibitors were the most prevalent.